2002
DOI: 10.1111/1469-7610.00226
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: The assessment of language pragmatics

Abstract: A core set of pragmatic assessment tools can be identified from the proliferation of instruments in current use. Further research is required to establish clearer norms and ranges in the development of pragmatic ability, particularly with respect to the understanding of inference, topic management and coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0
31

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(197 citation statements)
references
References 94 publications
(117 reference statements)
2
164
0
31
Order By: Relevance
“…The assessment of pragmatic abilities emerged as a central issue in the evaluation of patients with communicative impairments and related disorders in the early 1980s (e.g., Prutting, 1982), and the influence of pragmatic variables in treatment plans and goals has been more fully appreciated in the last 30 years. Pragmatic ability refers to a wide range of communicative behaviors concerning the way language is used in context to convey meanings (Adams, 2002;Bates, 1976; Kempson, 1975), and in the population of individuals with cerebral lesions, numerous patients have been found to have difficulties that lie principally with pragmatics. Patients typically show poor turn-taking skills and difficulty with topic maintenance, have problems understanding discourse and non-literal meanings, and may find it difficult to interpret subtle meanings or idiomatic statements and make knowledge-based inferences in social scripts (e.g., Dennis & Barnes, 1990; Friedland & Miller, 1998; McDonald, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of pragmatic abilities emerged as a central issue in the evaluation of patients with communicative impairments and related disorders in the early 1980s (e.g., Prutting, 1982), and the influence of pragmatic variables in treatment plans and goals has been more fully appreciated in the last 30 years. Pragmatic ability refers to a wide range of communicative behaviors concerning the way language is used in context to convey meanings (Adams, 2002;Bates, 1976; Kempson, 1975), and in the population of individuals with cerebral lesions, numerous patients have been found to have difficulties that lie principally with pragmatics. Patients typically show poor turn-taking skills and difficulty with topic maintenance, have problems understanding discourse and non-literal meanings, and may find it difficult to interpret subtle meanings or idiomatic statements and make knowledge-based inferences in social scripts (e.g., Dennis & Barnes, 1990; Friedland & Miller, 1998; McDonald, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed observation of pragmatic skills has been possible for many years, 21 but it is only with the development of the Children's Communication Checklist (CCC) that such data have been collected in population samples 22,23 and that such analyses have become feasible. Only 1 study, The Avon Longitudinal Study of Parents and Children, has combined both these measures, the CCC in middle childhood and the SDQ in adolescence.…”
mentioning
confidence: 99%
“…Speech-language therapists may be reluctant to assume roles regarding reading and writing for a variety of reasons such as their own perceptions, fear of change, and lack of training (Ehren & Ehren, 2001). In addition to this, standardised tests with adequate validity and norms are not always available for adolescents (Adams, 2002). In a more recent study Wellman (2006) of the University of Cincinnati (USA) suggested that educator collaboration with speech-language therapists exists in supporting secondary school learners with reading problems, but many educators still hold a more traditional view of speech-language therapists as working only with speech sound production.…”
mentioning
confidence: 99%